GRICE’S COOPERATIVE PRINCIPLE ON SATURDAY NIGHT LIVE TALK SHOW - SRI YULIANTI SRI; Hamzah A. Machmoed; Burhanuddin Arafah (JURNAL ILMU BUDAYA, 2021)
In doing interaction with other people, Cooperative Principle should be followed in order to make communication runs well and smoothly. Since in modern-day most of the information is passed on through written communication, and media play a noteworthy role within the conveyance of hot issues of the day, the language of the news has attracted the consideration of both media researchers and language specialists for decades. There are changes when people have to break Cooperative Principle in order to avoid offense and embarrassment. Farther, this research aims to find out kinds of maxim violations done by speakers on “Saturday Night Live” talk show. The result of this research found that there are twenty-two utterances that violated the maxim of Quality, the maxim of Quantity, the maxim of  Manner, and the maxim of  Relevance.